Marma Therapy - A Healing Touch for Pain with Gate Control Theory and Neuromodulation Technique (AYUSHDHARA, 2025)
Ayurveda is Indian traditional healing system. The science of Marma, is an holistic approach of Ayurveda for preventive and curative aspects of various diseases. Marma points are centres of Prana or vital force, when stimulated appropriately, Marmas can modify the functional conditions of body. Different techniques and procedures are used to stimulate Marma points. Prana or energy flow is channelise, leading to a state of physical, mental, and spiritual well-being. Marma therapy aims to provide instant relief from pain. Pain is defined as condition caused by stimuli that go beyond the intensity threshold for sensory nerve endings. Peripheral receptor activation triggers neuronal impulses, which induce pain within the higher cerebral centres. If someone is exposed to a painful (noxious) stimulus, administering a non-noxious stimulation by Marma therapy can help activate the gate control mechanism and reduce the sensation of pain. Marma therapy can be considered an ancient neuromodulation technique that emphasizes the connection between the body’s energy points and overall well-being. Neuromodulation is the alteration of nerve activity through targeted delivery of a stimulus to specific neurological sites in the body. In this article, the scholar attempts to explore the science behind Marma therapy and its effectiveness in the pain management. By harnessing the power of touch and energy, Marma therapy provides a healing touch for those seeking relief from pain and promotes overall wellness.